Voice of the Students: How Can the EU Take the Global Lead on Tackling Climate Change? - Costica Mihai; Alexandru Maxim; Constantin-Marius Apostoaie (CES Working Papers, 2017)
The EU has always been at the forefront of tackling environmental issues. This paper responds to the EU?s ,,call for action? towards addressing the issue of climate change – a key priority for the European Commission in the 2030 policy perspective. The topic is addressed through a focus group that seeks to identify and disseminate possible approaches through which the EU can leverage its international ,,actorness? in negotiating a straightforward and binding global agreement for action in climate change mitigation. The focus group involves a sample of students, beneficiaries of an environmentally focused Jean Monnet teaching module (TAG-EU). The diverse academic background of the students (coming from social, natural and exact sciences) provides a unique point of view in tackling this ardent issue and can bring valuable and interdisciplinary contributions to the discussion on climate change action.
Keywords: Q54; Q58; 330; climate change; EU policy; environmental protection; interdisciplinary approach